Halperin, Ehud. 2020. The Many Faces of a Himalayan Goddess: Hadimba, Her Devotees, and Religion in Rapid Change - Gairola, Vineet (Fieldwork in religion, 2023)
Halperin, Ehud. 2020. The Many Faces of a Himalayan Goddess: Hadimba, Her Devotees, and Religion in Rapid Change. Oxford and New York: Oxford University Press. iv + 270 pp. ISBN 9780190913588 (hbk). £79.